Pengetahuan tentang Keselamatan Kerja dan Perilaku Kesehatan Pekerja Salon Memengaruhi Kejadian Dermatitis Kontak: Sebuah Kajian - Aulia Rana Haerani; Kartini Kartini (CV. Ulil Albab Corp, 2023)
Salon workers are a profession with a fairly high level of exposure to chemicals, water and soap when doing his/her job in a beauty salon. These chemical ingredients or substances may be irritative, posing a risk of skin disorders such as contact dermatitis when exposure occurs for a long time and repeatedly. Brans et al stated the incidence of contact dermatitis in hairdressers was 56.1 to 97.4 cases per 10,000 workers a year. These skin disorders can degrade workers' skills impacting socioeconomic conditions and evoking negative emotions such as frustration, shame and depression. This can certainly reduce the quality of life of salon workers. Based on previous studies, it was concluded that health knowledge about workplace hazards and causes of disease and also good preventive attitudes could reduce the prevalence of occupational contact dermatitis. Health behaviors are also formed from knowledge and generate a positive attitude in responding to hazards in the work environment. Efforts are needed to increase salon workers' knowledge about the risk factors for health problems that may arise as a result of work and change individual confidence in wanting to wear personal protective equipment and increase self-efficacy which is beneficial in changing the behavior of a salon worker so as to support his health.